Determinants of Non-Insurance in A-Duiem Administrative Unit, White Nile State, Sudan 2018 - Samia Y. I. Habbani,; Egbal A. B. A. Karaig,; Elfatih M. Malik,; Sumaia M. Al-Fadil,; Maisa El-Fadul,; Siddik M. A. Shaheen,; Nahid A. A. Gadir,; Hashim Al-A. S. AbuZaid, (Public Health, 2025)
BackgroundPopulation knowledge and attitudes toward health insurance are important factors that facilitate health insurance coverage. Na-tional studies on these parameters are limited.AimThis study aims at assessing determinants of non-insurance in A-Duiem Administrative Unit and calculating as a secondary objective the household’s health insurance coverage.MethodsThe study was a descriptive cross-sectional community-based conducted in A-Duiem Administrative Unit, Sudan. It collected quantitative data from non-insured households and qualitative data by interviewing community leaders and conducting focus group discussions with community organizations members. Quantitative data analyzed using the Statistical Package for Social Sciences (SPSS) version 20, and the thematic analysis for the qualitative data.ResultsThe study interviewed 419 non-insured households’ heads and thirteen community leaders and conducted eight focus group discussions with sixty community organizations members. Around 37.9% (95% CI: 33.4-42.7) of the heads of the non-insured households did not know the health insurance, while only 2.4% (95% CI: 1.5-4.7) had good knowledge. The knowledge of non-insured community leaders and members of the community organizations was moderate. The study participants showed positive attitudes towards health insurance, as 97% (95% CI: 95.1-98.4) of the heads of the non-insured households wanted to join the health insurance and 65% (95% CI: 59.2-70.1) of them stated that they could pay its premium. Most of the com-munity leaders and members of the community organizations had health insurance cards. Those who were not enrolled, have limited knowledge about health insurance while almost all believe they should join it. The study identified 52.4% of non-insured households (95% CI: 48.9-55.8). The study showed low health insurance coverage among families, despite their positive attitude. This is mostly attributed to poor awareness of the heads of the non-insured households about health insurance. The National Health Insurance Fund (NHIF) should address this gap through effective communication strategies using motivated community institutions.